Hydroxytyrosol and tyrosol sulfate metabolites protect against the oxidized cholesterol pro-oxidant effect in Caco-2 human enterocyte-like cells. Issue 1 (21st October 2015) - Atzeri, Angela; Lucas, Ricardo; Incani, Alessandra; Peñalver, Pablo; Zafra-Gómez, Alberto; Melis, M. Paola; Pizzala, Roberto; Morales, Juan C.; Deiana, Monica
Abstract : Hydroxytyrosol and tyrosol sulfate metabolites counteract the oxidizing action of oxidized cholesterol in Caco-2 cells with an efficiency comparable to that of the parent compounds. Abstract : The aim of this study was to investigate the ability of the sulfate metabolites of hydroxytyrosol (HT) and tyrosol (TYR) to act as antioxidants counteracting the pro-oxidant effect of oxidized cholesterol in intestinal cells. For this purpose, we synthesized sulfate metabolites of HT and TYR using a chemical methodology and examined their antioxidant activity in Caco-2 monolayers in comparison with the parent compounds. Exposure to oxidized cholesterol led to ROS production, oxidative damage, as indicated by the MDA increase, a decrease of reduced glutathione concentration and an enhancement of glutathione peroxidase activity. All the tested compounds were able to counteract the oxidizing action of oxidized cholesterol; HT and TYR sulfate metabolites showed an efficiency in protecting intestinal cells comparable to that of the parent compounds, strengthening the assumption that the potential beneficial effect of the parent compounds is retained, although extensive metabolisation occurs, the resulting metabolites being able to exert a biological action themselves.